Numerical Study on Spout Elevation of a Gas-Particle Spout Fluidized Bed in Microwave-Vacuum Dryer - Jin, G.; Zhang, M.; Fang, Zhongxiang; Cui, Z.; Song, C. (Elsevier Ltd, 2014)
The dynamic characteristics of gas-particle spout fluidized bed in a pulsed spouted microwave-vacuum drying system (PSMVD) were investigated. The spout fluidization process in a pseudo-2-D spout fluidized bed was simulated by computational fluid dynamics (CFD) using the inviscid two-fluid theory method (TFM) based on the kinetic theory of granular flow. The dynamic characteristics of the spout fluidized bed and the effect of spout elevation on the particle movement were revealed, which could be used to improve the uniformity of particle mixing and microwave heating. The mathematical model demonstrated that the spout fluidization process includes isolated, merged and transitional jets and the fluidization at a specific spout gas velocity has a start-up stage and a quasi-steady fluidization stage. The spout velocity was an important factor controlling particle status in the spout fluidized bed and a critical velocity was identified for effect transition of the flow pattern. There was an approximately linear correlation between the jet penetration depth and the spout velocity. When the spout gas velocity increased up to the critical velocity region, the pressure drop tended to convert from negative pressure to positive pressure.